Pengembangan Sikap Sosial dalam Pembelajaran Biologi: Kajian Potensi Pembelajaran Kooperatif - Mursito S. Bialangi; I Nengah Kundera (Universitas Sebelas Maret, 2018)
The development of social attitude is done as an effort in preparing students to compete for a better future. Good learning outcomes can be obtained through ideal learning. The expected demands in the 2013 curriculum related to social attitudes, it is necessary to be developed, as a means of students to compete in the future. Mastering and developing students' social attitudes is done to help students achieve good learning outcomes. It is hoped that classroom learning integrates these social attitudes. In accordance with the fact that the current biology learning is generally still focused on improving students' cognitive learning outcomes, while developing students' social attitudes has not been done completely This paper is a literature review to analyze the development of students' social attitudes in Biology learning. Based on the results of literature review, it is known that conventional learning model applied can not develop social attitudes maximally. Types of social attitudes include honesty, discipline, attitude of responsibility, tolerance, mutual cooperation, modesty, and self-confidence. Student social attitude is important to develop and possess students in learning, because it is very closely related to aspects that must be mastered by students, in order to achieve the expected learning outcomes. The development of students' social attitudes is very important, especially by educators, in particular. and generally by the Master, through the application of appropriate learning models. Based on the results of relevant research and literature review reveal the potential of cooperative learning model to develop students' social attitudes in classroom learning activities. It is suggested to educators to develop students' social attitudes as well as to promote improved learning outcomes, and social attitudes expected to be held by students as the basic capital for life in the future.